Dinamika Psikologis Remaja Korban Perceraian: Sebuah Studi Kasus Kenakalan Remaja - Ardian Praptomojati (Universitas Andalas, 2018)
Parental divorce can be a very stressful experience for adolescents. Adolescents will lose their parent figure and feel different atmosphere in the family. This study aimed to identify the psychological dynamics of adolescents that have experienced parental divorce developing into juvenile delinquency. This was a case study research. The subject of this study was a 13-year-old boy with divorced parent and lived in an orphanage. Data were collected through observations, interviews, and psychological tests. The result revealed that juvenile delinquency happens because of the need of gaining attention from others. The wrong mindset